Investigação in vitro e in vivo do efeito regenerativo na medula espinal na presença de fragmentos do nervo isquiático com adição dos óleos essenciais de hyptis suaveolens (l.) poit e croton blanchetianus baill - Fernandes, Luciana Cristina Borges (Universidade Federal Rural do Semi-Árido, 2020)
The spinal cord (SC) is affected in cases of direct or indirect trauma and some studies indicate that the peripheral nerves induce an environment conducive to regeneration. In addition, several medicinal plants have secondary metabolites with activities in the central nervous system. This study aimed to analyze the regenerative effect on SC in vitro and in vivo in the presence of sciatic nerve fragments (SNFG) with the addition of essential oils (EOS) from Hyptis suaveolens (HS) and Croton blanchetianus (CB). The HS and CB plants were submitted to the hydrodistillation process and the analysis of the chemical composition of the EOS was perfomed by gas chromatography and mass spectrometry. For the evaluation of cellular plasticity on SC in vitro, the SC cells were collected from newborn Wistar rats, and then cultured in six groups: one control (D-10) and the others with different combinations of sciatic nerve conditioned medium (SNCM) and HS and CB EOS. Cell morphometry was evaluated after 96 hours by phase contrast microscopy, and then the mmunocytochemistry was performed for GFAP, GAP-43, NeuN and plasticity was performed by scanning electron microscopy. The groups were statistically compared using the Tukey and Bonferroni tests (p <0.05). Thus, it was possible to evaluate the adherence, the plastic and trophic effect in groups cultured in D-10 plus EOS, with more visible morphological changes when compared to control groups. CB EO, especially, promoted the maintenance of cell expansion, indicating its action on the plasticity of SC cells. Regarding the regenerative analysis on SC in vivo, forty Wistar rats were used; sciatic nerve was removed from four animals, and thirty-six animals were submitted to a 4 mm thick medullary transection at the lower thoracic level; the animals were later separated in 6 groups (n=6): in group 1, 10μl of saline solution (5%)(SS); in group 2, FGNS plus 10μl of SS (SS + NS); in group 3, FGNS plus HS essential oil (EO) (HS + NS); in group 4, only HS EO; in group 5, FGNS plus CB EO (CB + NS) and in group 6, only CB EO (CB + NS) were inoculated. Posterior limb performance was assessed weekly for 12 weeks, using motor behavior score (BBB) and functional deficit associated with combined score behavior (CBS). Data from the behavioral tests of the treated groups were compared statistically. The different types of treatments allowed the recovery of the hind limbs movements of the animals of the FGNI and OES groups, and they showed a better recovery when compared to the SS and SS + NS groups. However, the groups with the EO of CB showed more significant results and superiority compared to the groups with the EO of HS. Therefore, the combination of OES and peripheral nerves such as NI, in vitro and in vivo, provided morphological plasticity and an improvement in the functional recovery of SC.
Keywords: Nervo ciático; Metabólitos secundários; Trofismo; Neuroproteção; Regeneração nervosa; Sciatic nerve; Secondary metabolites; Trophism; Neuroprotection; Nerve regeneration; CIENCIAS AGRARIAS::MEDICINA VETERINARIA